Causal Factors Influencing Risk Management of Electronic Commerce for Small and Medium Enterprises in The Central Region of Thailand - Wongkham, Anantaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2021)
The objectives of this research were: (1) to study causal factors influencing the risks of e-commerce for small and medium enterprises, (2) to study management of risks influence of e-commerce for small and medium enterprises and (3) to suggest causal factors influencing risk management of e-commerce for small and medium enterprises. This research was a quantitative research using questionnaires as a tool to collect data. The sample consisted of 400 people using the formula of Cochran (1953). The statistics used for data analysis were percentage, mean, standard deviation, Pearson’s correlation coefficient and analyzed the structural equation modeling: SEM. The results found that: Findings from the research suggested that information technology, consumer behavior and information security had direct and positive influence on enterprise risk management. By examining the construct validity of information technology model consists of 4 components: data devices network and personnel the research founded the information technology model is consistent with the empirical data. Examining the construct validity of consumer behavior model which consists of 3 components: attitude user interface quality and security perception the research founded the consumer behavior model is consistent with empirical data. Examine the construct validity of security model which consists of 3 components: confidentiality integrity and availability the research founded the security model is consistence with empirical data. The examining the construct validity of enterprise risk management model which consists of 4 components: communication support from top management trust and organization structures the research founded the enterprise risk management model is consistent with empirical data. In addition, information technology was indirectly influenced by enterprise risk management by passing on consumer behavior and security. Consumer behavior was indirectly influenced by enterprise risk management by passing on security. In enterprise risk management model, the research founded the most influential variables in enterprise risk management were information technology consumer behavior and information security, respectively. Article history: Received 14 November 2020 Revised 22 January 2021 Accepted 1 November 2021 SIMILARITY INDEX = 0.00 %